2023
DOI: 10.1002/fsn3.3275
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous Sudanese sorghum‐based food: Secondary metabolites and antioxidant activities of traditional Sudanese nonalcoholic beverage Hulu‐mur from two sorghum landraces

Abstract: Hulu‐mur is a Sudanese traditional nonalcoholic beverage that is made from sorghum flour. This work determined the secondary metabolites and antioxidant activities of traditional Sudanese nonalcoholic beverage Hulu‐mur from two local sorghum landraces Abjaro and Hegarii. The changes on the total phenolic content (TPC), total flavonoid content (TFC), carotene content, tannins, and antioxidant activity (DPPH, reducing power, and FRAP) were estimated during the preparation of the Hulu‐mur flasks. For both landrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…Due to their significant interaction with starch and particularly amylose, polymeric tannins are key in producing resistant starch. The tannin oligomers present human health benefits through their immunomodulatory, antiradical, vasodilatory, cardioprotective, antithrombotic, and anti-UV actions [ 47 , 48 , 49 ]. Others potential health benefits are risk reduction for obesity, dyslipidemia, hypertension, and promoting urination and blood circulation [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to their significant interaction with starch and particularly amylose, polymeric tannins are key in producing resistant starch. The tannin oligomers present human health benefits through their immunomodulatory, antiradical, vasodilatory, cardioprotective, antithrombotic, and anti-UV actions [ 47 , 48 , 49 ]. Others potential health benefits are risk reduction for obesity, dyslipidemia, hypertension, and promoting urination and blood circulation [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported improved chemical, functional, and nutritional properties of sorghum-based snacks fortified with mung bean ( 19 ). Furthermore, Abdelhalim et al ( 20 ) reported high levels of total phenolic content (88.7 mg GAE/g) and total tannin content (9.2 mg CE/g), as well as strong antioxidant properties, in a sorghum-only beverage. Several recent reviews provide detailed information on a wide variety of sorghum-based functional foods ( 7 , 21 ).…”
Section: Introductionmentioning
confidence: 99%